Suppression of hnRNP A1 binding to HK1 RNA leads to glycolytic dysfunction in Alzheimer’s disease models - Ji, Xin-Hao; Liu, Ting-Ting; Wei, Ai-Hong; Lei, Hui-Ping; Chen, Yue; Wu, Ling-Nan; Liu, Ju; Zhang, Ying; Yan, Fei; Chen, Mei-Xiang; Jin, Hai; Shi, Jing-Shan; et al. (Frontiers in Aging Neuroscience, 2023)
Brain glycolytic dysfunction is closely related to the development of Alzheimer's disease (AD), and abnormal transcriptional regulation of hexokinase 1 (HK1), a key enzyme of glycolysis, has not been elucidated in the pathology of AD. We found decreased heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) expression in 3×Tg-AD mice and Aβ25-35-induced HT22 cells, suggesting its involvement in AD pathogenesis. Overexpression of hnRNP A1 improved Aβ25-35-induced HT22 glycolytic impairment and neuronal death by enhancing HK1 expression. CLIP-qPCR showed that hnRNP A1 was significantly enriched with mRNA of HK1. Inhibition of the RNA binding domain (RBD) of hnRNP A1 inhibited the expression level of HK1 mRNA, leading to impaired glycolytic function and neuronal cell death. Furthermore, we demonstrated that inhibiting RBD of hnRNP A1 binding to RNA of amyloid precursor protein (APP) resulted in increased Aβ deposition, whereas Aβ25-35 inhibits hnRNP A1 expression by enhancing phosphorylation of p38 MAPK in HT22 cells, suggesting a bidirectional regulation between hnRNP A1 and Aβ. In conclusion, our findings suggested that hnRNP A1 played a key regulatory role in glycolytic dysfunction and Aβ deposition in AD models, hnRNP A1 may be an important target for the treatment of AD.